Accountability in the Internet Era: A Lesson from Local Governments in Indonesia - Habib Muhammad Shahib; Firman Rato Risky (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2017)
Nowadays, Indonesia is one of the countries with the highest internet user growth. In line with it, the local governments in Indonesia use their official website to report the government’s activities as an accountability form to the society. Thus, this study conducted for knowing the accountability characteristics and the factors that affect the level of internet accountability reports in the local government websites.Using content analysis based on Global Reporting Initiative (GRI) index in government agencies and OLS statistical approach on the 34 provinces’ official websites, this study finds, in general, the provinces’ websites have reported 63% of the total numbers that suggested by GRI. Furthermore, there are two main factors, i.e. the number of population and districts/cities, which positively affect the level of accountability reports in provinces’ website. However, no empirical evidence shows the press pressure affects the broad of website reporting in the Indonesia provinces context.Overall, this research indicates that the Indonesia local governments, in this case, provincial governments have focused on delivering their accountability to the society. Moreover, this is a good sign for the democracy growth in Indonesia. Furthermore, the Indonesia local governments may have to give more portions on their official website for answering the headline news from the mass media, specifically for the environmental and social themes. Therefore, it will further strengthen the governance-sustainability and democracy in Indonesia local government environment.